Failure of aluminium metal spray/organic duplex coating systems on structural steel. (November 2013) - Sumon, T. A.; Lyon, S. B.; Scantlebury, J. D.
Abstract : Individually, aluminium metal spray (AMS) and organic paints are well established as effective protective coatings for steel substrates. These coatings are also frequently used together as duplex systems where their combination should produce a synergistic effect. However in certain, mainly marine, environments premature failure of such coatings, involving early blistering of the paint, has been observed in service after 3–5 years. This work aims to understand the mechanisms associated with the early failure of the AMS+paint duplex system. Various panels were initially prepared for accelerated exposure using combinations of coatings on blast cleaned steel. Visual inspection after salt spray exposure revealed the presence of white corrosion product, which was confirmed afterwards as Al(OH)3 . Observation of the coating microstructures before and after salt spray exposure confirmed significant local corrosion of aluminium underneath the paint layer. It is suggested that failure of the duplex AMS/paint system initiates by corrosion of the porous AMS underneath the organic layer then progresses by the combined effect of volume expansion due to formation of Al(OH)3 and cathodic blistering of the paint from the AMS surface.